Gambaran Faktor-Faktor Stres Kerja Caregiver dalam Melayani Pasien Gangguan Jiwa di Yayasan Galuh Kota Bekasi 2017 - Anderias Ambe Ando; Ahmad Farid Umar; Agustina Agustina (STIKes Persada Husada Indonesia, 2017)
Job stress is a feeling that suppresses employees in facing workload. Mental disorders are health irregularities with psychological manifestations or behaviour related to real sufferings and poor performance. Caregivers are formal and informal, such as patient care at place of residence or homes. Aim of this research is to describe the factors that influence the caregiver's work stress in serving mental patients at Galuh Foundation Bekasi Town year 2017. This research applied phenomenological qualitative approach. Samples were from 6 people, i.e. 4 nurses/caregivers at the Foundation and 2 patients' family caregivers. Data collection by in-depth interviews, observations and document reviews. Research results showed role conflict that occurs i.e. there is fear, worry towards aggressive patients, especially newly admitted patients. Interpersonal conflict i.e. feelings of annoyance, angered and yet feeling pity towards patients. Caregivers' volume and variation of work load Is very complex added the duties, functions and responsibilities of the caregiver towards the work are quite large and are at risk because they are responsible for taking care (taking medicine, hygiene, exercise, rests, meals, group activities) a large number of patients who are also mostly unruly and difficult to control, as well also responsibility for environmental cleanliness. The magnitude of this responsibility can cause stress to the caregiver's work. According to the caregivers, the condition of Galuh Foundation environment is inadequately comfortable, unhygienic, humid, noisy and very crowded with patient activities due to the large number of patients in a limited space thus resulting in causing stress on the caregivers' work.